2010
DOI: 10.1158/1535-7163.mct-09-0960
|View full text |Cite
|
Sign up to set email alerts
|

Potent Preclinical Impact of Metronomic Low-Dose Oral Topotecan Combined with the Antiangiogenic Drug Pazopanib for the Treatment of Ovarian Cancer

Abstract: Low-dose metronomic chemotherapy has shown promising activity in many preclinical and some phase II clinical studies involving various tumor types. To evaluate further the potential therapeutic impact of metronomic chemotherapy for ovarian cancer, we developed a preclinical model of advanced human ovarian cancer and tested various low-dose metronomic chemotherapy regimens alone or in concurrent combination with an antiangiogenic drug, pazopanib. Clones of the SKOV-3 human ovarian carcinoma cell line expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 53 publications
4
93
1
2
Order By: Relevance
“…The association of CLM3 with SN-38, the active metabolite of irinotecan, showed a marked synergistic effect on endothelial and cancer cells, placing our compound on the same level as those currently being tested for combination chemotherapy regimens, such as vandetanib [48], pazopanib [49] and axitinib [39]. In order to improve the antineoplastic activity of CLM3, we presently investigated the effects of CLM3 in combination with SN-38 in EGFR and VEGFR-2 expressing human endothelial cell line HMVEC-d and in EGFR and RET expressing human thyroid cancer cell 8305C [50].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The association of CLM3 with SN-38, the active metabolite of irinotecan, showed a marked synergistic effect on endothelial and cancer cells, placing our compound on the same level as those currently being tested for combination chemotherapy regimens, such as vandetanib [48], pazopanib [49] and axitinib [39]. In order to improve the antineoplastic activity of CLM3, we presently investigated the effects of CLM3 in combination with SN-38 in EGFR and VEGFR-2 expressing human endothelial cell line HMVEC-d and in EGFR and RET expressing human thyroid cancer cell 8305C [50].…”
Section: Discussionmentioning
confidence: 88%
“…irinotecan and topotecan) and tyrosine kinase inhibitors (TKIs; i.e. pazopanib, axitinib and sunitinib) appears not only possible but very promising based on the involved pharmacodynamic mechanisms of their synergism [39,49]. Even though it is still premature to predict the clinical perspective for the new compound CLM3, the possible immediate clinical significance of our results is the development of a rational strategy for irinotecan/TKIs combination.…”
Section: Discussionmentioning
confidence: 90%
“…LDM chemotherapy has lower acute toxicity due to lower exposure of the cytotoxic agents. It has been shown active in diverse tumor types, including metastatic disease, especially when combined with antiangiogenic drugs (27)(28)(29)(30). The availability of the oral topotecan, along with our previous studies combining metronomic topotecan with pazopanib in neuroblastoma preclinical models (23), suggest that oral metronomic topotecan may be an ideal candidate for pediatric solid tumors.…”
Section: Introductionmentioning
confidence: 97%
“…They demonstrated that combining pazopanib (Votrient s ; GlaxoSmithKline), a VEGF receptor inhibitor, with metronomic TPT, is synergistic and resulted in 100% survival of the drug combination (but not the individual monotherapies) after 6 months of continuous therapy in an aggressive, metastatic, orthotropic xenograft ovarian model. 122 Two orthotropic ovarian cancer model studies showed that combining pazopanib with metronomic TPT is synergistic and resulted in a significant improvement in survival vs. the individual monotherapies. 123 Burkitt et al at the University of Michigan Comprehensive Cancer Center demonstrated that genetic disruption of both HIF-1a and HIF-2a had synergistic anti-tumour activity when combined with sunitinib in a colorectal xenograft model.…”
Section: Combination Therapymentioning
confidence: 99%